Ki Hadjar dewantara’s trikon principels towards the development of indonesian education - Burhan Kurniansyah; Sofyan Sauri; Pupun Nuryani (Sekolah Pascasarjana UPI, 2023)
Ideas are ideas resulting from one's thoughts. The idea here is the idea of Ki Hadjar Dewantara as the father of Indonesian Education and is also one of Indonesia's national heroes. One of the ideas of Ki Hadjar Dewantara is about the principle of Trikon cultural theory (Continuity, Convergence and concentricity) is the concept of Ki Hadjar Dewantara culture which has always been the basis of thinking today in the process of cultural development in Indonesia. This research uses a qualitative approach with descriptive analysis. Data collection using library research. As for the qualitative research instrument itself, the researcher (human instrument). This study aims to explore the relevance of the basic idea of Trikon Ki Hadjar Deawantar to the development of Indonesian education which continues to this day and dynamically continues to move towards the ideal achievement goal of education. That the Principle of Trikon Ki Hadjar Dewantara has development value in the educational process.